Pengaruh real activities manipulation, opinion shopping, dan sales growth terhadap penerimaan opini audit going concern - Dian Widiyati; Annafisa Alfiah (LPMP Imperium, 2023)
This study aims to determine the effect of real activities manipulation, opinion shopping, and sales growth on the receipt of audit opinions in Industrial Companies listed on the Indonesia Stock Exchange for the 2016-2020 period. The sampling technique uses the purposive sampling method; the samples obtained are as many as 23 Industrial companies for five years registered on the IDX with a total observation of 115 financial statement data. The hypothesis testing method in this study was tested using descriptive statistical analysis and logistic regression analysis using Eviews version 10. The results of this study show that partially real activities manipulation does not affect the receipt of audit opinion going concern, opinion shopping involves the receipt of audit opinion going concern, and sales growth does not affect the receipt of audit opinion going concern. Public interest statement This study could give insight for company to handling audit opinion through the policy of choosing public accounting firm. The company should follow the rules that regulate in Indonesia.